2012
DOI: 10.1111/all.12055
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase‐4 inhibition improves corticosteroid insensitivity in pulmonary endothelial cells under oxidative stress

Abstract: Combination of rolipram and dexamethasone shows additive properties in HPAECs under glucocorticoid insensitive conditions. These results may be of potential value in future anti-inflammatory therapies using combination of PDE4 inhibitors and glucocorticoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 43 publications
(62 reference statements)
0
17
0
Order By: Relevance
“…Other studies have reported additive effects of cAMP elevating agents on both expression and activation of the glucocorticoid receptor (GR), including both β 2 agonists and PDE4 inhibitors (Ortiz et al. 2012; Roth et al. 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reported additive effects of cAMP elevating agents on both expression and activation of the glucocorticoid receptor (GR), including both β 2 agonists and PDE4 inhibitors (Ortiz et al. 2012; Roth et al. 2002).…”
Section: Discussionmentioning
confidence: 99%
“…PDE4 inhibitors have proven potential as anti-inflammatory drugs in chronic airway diseases. By increasing intracellular cAMP levels, PDE4 inhibitors elicit a broad spectrum of antiinflammatory effects, including the suppression of the release of mucins (Mata et al 2005), inflammatory cytokines, and other mediators (Buenestado et al 2011;Burgess et al 2006;Ouagued et al 2005), and also inhibit the actions of reactive oxygen species which are proinflammatory in nature (Brown et al 2007;de Visser et al 2011;Ortiz et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These metabolites have regulatory and homeostatic functions and participate in the complicated inflammatory processes of airway eosinophilia, edema, hypersecretion of mucus, remodeling, and AHR observed in patients with airway diseases (40,41).…”
Section: Arachidonic Acid Metabolitesmentioning
confidence: 99%
“…Another study [13] showed that cigarette smoke inhibited HDAC activity in human pulmonary artery endothelial cells. In a study of 49 COPD patients and 42 healthy controls, HDAC2 mRNA and protein expression was found to correlate with development and prognosis of COPD, suggesting it could be used as a biomarker.…”
Section: Expression Of Histone Deacetylases Enzymes Chronic Respiratomentioning
confidence: 99%